Plant Production Protocols from Seeds of Threatened Atropa baetica and Widespread A. belladonna, Both Rich in Alkaloids - Elena Copete; Miguel A. Copete; Esmeralda Martínez-Duro; Alejandro Santiago; Pablo Ferrandis; José M. Herranz (Life, 2023)
Members of the genus Atropa contain various tropane alkaloids, including atropine ((±)-hyoscyamine) and scopolamine, which possess medicinal properties. Preserving the diverse genetic background of wild populations via optimal plant production from seeds could be essential for avoiding the loss of potential uses. We analyzed the germination ecology of two Atropa species comprising the threatened A. baetica and widespread A. belladonna to determine the: (1) influence of temperature, light, and seed age on germination patterns; (2) effects of cold stratification and gibberellic acid (GA3); (3) phenology of seedling emergence in outdoor conditions; (4) phenology of dormancy break and loss of viability in buried seeds; and (5) ability to form persistent soil seed banks. Freshly matured seeds exhibited conditional physiological dormancy, with germination at high temperatures (32/18 °C) but not at low and cold ones (5, 15/4, 20/7 °C). The germination ability increased with time of dry storage and with GA3, thereby suggesting nondeep physiological dormancy. Under outdoor conditions, no seedlings emerged during the first post-sown autumn, but emergence peaks occurred in late winter–early spring. Both species could form small persistent soil seed banks with short durations (3–5 years). A plant production protocol from seeds was established for both taxa.